Effect of Preservatives Upon Sensory Properties of Laboratory Biscuit During Storage - Baghdad Science Journal (مجلة بغداد للعلوم)
The study was conducted to detect the effect of addition of 0.03, 0.06 and0.10% potassium sorbate and 0.10, 0.15, 0.20 and 0.30% sodium propionate upon the sensory properties of laboratory made biscuit. The statistical analysis of the results revealed no significant differences (P